The Effect of Reading Interest on Learning Outcomes among High School Students - Isti Ainun; Prio Utomo; Ibnu Maulana (Jurnal Indonesia Pendidikan Profesi Guru, 2026)
Background: Low student learning outcomes are often associated with low reading interest. Reading interest plays an important role in improving students’ understanding, knowledge, and academic achievement. Therefore, increasing students’ reading interest has become an important concern for teachers and schools. Objective: This study aimed to determine the effect of reading interest on students’ learning outcomes and to identify its contribution to learning achievement. Method: The study employed a correlational associative research design. The research was conducted at SMA Plus Merdeka Soreang during the 2024 academic year. The sample consisted of 38 second-grade students selected using a population sampling technique. Data were collected using reading interest and learning outcomes questionnaires and analysed using Pearson correlation analysis and simple linear regression. Result: The findings revealed a significant positive relationship between reading interest and students’ learning outcomes, with a correlation coefficient of 0.747 and a significance value of 0.000. Conclusion: The study concludes that reading interest strongly influences students’ learning outcomes. Contribution; This research underscores the importance of literacy development programs in improving students’ academic achievement.